CREACIÒN DE UNA RUTA TURÌSTICA Y SU INCIDENCIA EN EL TURISMO RURAL DE LA COMUNIDAD CAZHAPUGRO- PARROQUIA LUDO-CANTÒN SIGSIG-PROVINCIA DEL AZUAY AÑO 2022 - Pincay Fernandez, Juliana Julissa (2022)
The present work Creation of a tourist route of the Cazhapugro Community, Ludo Parish, Canton Sígsig, Province of Azuay, Year 2022 seeks to strengthen the rural tourism of the community by creating routes, analyzing, identifying points of tourist attraction in the sector, this occurred through field research and documentary research, in order to identify the main shortcomings that the community has, in order to solve this problem, community tourism management strategies will be used, through the application of tools such as Promotion, Advertising, Conservation of the Environment, the same ones that allow generating activities or programs, with the purpose of increasing the tourist activity in the aforementioned Community, etc. For this work, the inductive and deductive research methods were also used. research such as the survey, the interview, in order to re compile information, statistical assessments were also applied such as: tables and graphs. With the implementation of this methodology, it was possible to validate the hypothesis and to elaborate the tourist promotion plan of the natural and cultural attractions of the community that contains the management tools in tourism with the objective of creating awareness in the inhabitants of caring for the natural and cultural environment. that surrounds them under the criteria of good living stipulated in the Constitution with the exposed degree thesis seeks to create a tourist route in the Cazhapugro Community, for which 300 inhabitants of the sector were taken as a research sample, in which regulations will be developed that regulate the activities scheduled jointly at the time of working, under the guidelines of rurality, but this in turn requires that options and alternatives be generated through initiatives, for the benefit of the community, thus considering this project as one more impulse for the generation of new proposals.